COVID-19 and Domestic Animals: Exploring the Species Barrier Crossing, Zoonotic and Reverse Zoonotic Transmission of SARS-CoV-2 - Kumar, Rajesh; Harilal, Seetha; Al-Sehemi, Abdullah G.; Pannipara, Mehboobali; Behl, Tapan; Mathew, Githa E.; Mathew, Bijo (Current Pharmaceutical Design, 2021)
Background: To date, more than thirty animals have been tested positive for SARS-CoV-2; all of them infected by humans with COVID-19. Some animal experiments suggested the possibility of animal to animal transmission of SARS-CoV-2 that was seen in some cases of infected animals. Animal to human transmission was considered unlikely until investigations revealed the possibility of mink to human transmission of SARS-CoV-2 in the Netherlands. 1 Objective: The current study aims at highlighting the predominance of SARS-CoV-2 infection in various animal species, reverse zoonotic transmission and proposing possible animal models that might aid in the study and development of a vaccine against Covid-19. Methods: The authors have gathered information on various animal species infected with SARS-CoV-2 and possible tests conducted via online news reports, websites and Scopus indexed journals. Results: The study of the susceptibility of SARS-CoV-2 to domestic animals concluded that pigs, chicken, and ducks were not vulnerable to Covid-19; dogs showed less susceptibility to SARS-CoV-2 and cats as well as ferrets were seen susceptible to Covid-19. SARS-CoV-2 has been seen crossing the species barrier, infecting humans from the wild with the yet unclear source, spreading from humans to humans quickly, humans to animals, animals to animals, and is likely to spread from animals to humans even though minimally. Animals appear somewhat resistant to SARS-CoV-2 transmission compared to humans who globally crossed eight million infection cases, and the infected animals mostly do not show many complications and recover quickly. Conclusion: Precautions are advised to prevent human to animal transmission of the virus, and in some areas, to avoid animal to human spread of the virus. Further monitoring is required to assess the SARS-CoV-2 infection in animals as COVID-19 is a rapidly evolving condition worldwide. Cats and ferrets have physiological resemblance and genome sequencing studies propose the possibility of these species to be used as animal models for investigating the SARS-CoV-2 infection and this might aid in further studies and vaccine development against Covid-19.
Keywords: SARS-CoV-2